ISOLASI DAN REGENERASI PROTOPLAS DARI MESOFIL DAUN KENT ANG (Solanum tuberosum L) DIHAPLOID - Agus Purwito; G. A. Wattimena; Antonius Suwanto; Inez H.S. Loeddin Suharsono; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1999)
The isolation and regeneration of potato (Solanum tuberosum L) protoplasts have been carried out. Mesophyl cell protoplast were isolated from two dihaploid cultivars of potato BF 15 and SVP 10 leaves used four different enzymes solution. Protoplast were cultured onto four different cultures media to increase plating efficiency. Calli were then transferred to ten different regeneration media. Using cellulose RS 0.5 % and pectolyase Y-23 0.05 % protoplast yield of both cultivars were improved. Medium VKM  supplemented with 0.2 mg/l 2, 4-D, 1.0 mg/l NAA and 0.5 mg/l zeatin or 2iP were increase recovery of colonies from protoplast up to 5.9%. Regeneration medium containing zeatin did always produce more shoots than those of 2iP. Genotypes dependant regeneration frequencies have also been showed in this experiments